Inside debt, bank default risk, and performance during the crisis - Bennett, Rosalind L.; Güntay, Levent; Unal, Haluk (Journal of Financial Intermediation, 2015)
In this paper, we examine whether the structure of the chief executive officer’s (CEO) compensation package can explain default risk and performance in bank holding companies (BHCs) during the recent credit crisis. Using a sample of 371 BHCs, we show that in 2006 higher holdings of inside debt relative to inside equity by a CEO after controlling for firm leverage is associated with lower default risk and better performance during the crisis period. We present evidence that before the crisis banks with higher inside debt ratios also have supervisory ratings that indicate stronger capital positions, better management, stronger earnings, and being in a better position to withstand market shocks in the future. Such ex-ante evidence can explain the observed relationship between inside debt, default risk, and performance during the crisis.